Using the Lean Process to Achieve Skin‐to‐Skin after Cesarean Births. Issue 1 (June 2015) - Price, Kim; Weaver, Jackie; Tribbett, Stacey B.; Carpenter, Christine
<x xml:space="preserve">Abstract</x> Poster Presentation Purpose for the Program To use Lean improvement methods to improve a clinical process: facilitating skin‐to‐skin contact between the mother and newborn after cesarean birth. Proposed Change The goal of this project was to establish a process to facilitate keeping the mother and newborn together and provide skin‐to‐skin contact in the operating room or recovery room after cesarean birth. Previously, we separated the mother and newborn and moved the newborn to the nursery for assessment while the mother remained in the birth center, which delayed skin‐to‐skin contact. Implementation, Outcomes, and Evaluation Lean improvement project team members included process engineers, nurses, managers and director. Lean methods used included spaghetti mapping, Gemba walks, and identification of process waste. Following a plan, do, check, act (PDCA) trial, the team identified the following issues: resistance from anesthesiologists, ; confusion regarding communication paths, and a need for educational tools to clarify the process and contraindications. Anesthesiologists were provided with published evidence and the opportunity to discuss their concerns with physician colleagues at another hospital who were already providing skin‐to‐skin contact in the operating room. Posters outlining the communication paths and process changes for each area were provided. The team determined criteria for contraindicating participation in skin‐to‐skin contact and designed process maps for complicated versus uncomplicated births. Project outcomes include changes in work function, which enables the newborn nurse to be the newborn response nurse, enhanced communication between the clinical areas, and the establishment of a transitional nursery within the neonatal nursery. Participation empowered staff to initiate changes related to nurse station redesign for improved work flow and development of a Baby Passport to assist with discharge preparation. During the 1‐month PDCA trial, skin‐to‐skin after cesarean increased from 0% to 15% overall. Continued focus will be on monitoring exclusive breastfeeding rates, initiation and duration of skin‐to‐skin contact, staff education, and quality review. Implications for Nursing Practice The 10 Steps to Successful Breastfeeding from the Baby Friendly Hospital Initiative through the World Health Organization (WHO) and UNICEF include the initiation of breastfeeding within 1 hour of birth. By minimizing separation of mothers and newborns after a cesarean, breastfeeding can occur sooner. Skin‐to‐skin contact between the mother and newborn provides improved infant temperature, more stable glucose regulation, and increased maternal bonding. The use of Lean methods for improvement to provide skin‐to‐skin contact resulted in improved processes and empowered nurses to identify additional improvement opportunities.